PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL PEMAKNAAN PADA MATERI GELOMBANG DAN BUNYI UNTUK MELATIHKAN SENSITIVITAS MORAL SISWA SMP - Abdul Hamid Sudiyono; Wahono Widodo; Endang Susantini (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This research was aimed to produce a valid, practical, and effective teaching material using œinternalization model on subject matter ˜wave and sound, to increase moral sensitivity of student in Junior High School. The development of it used 4-D model which was reduced to 3-D, that is ˜define, design, and develop, and was try outed on grade VIII of SMP Negeri 1 Ketapang using One Group Pretest and Posttest Design. The data collection consisted of observation, test, documentation, and questionnaire. The data analysis technique used in the study was descriptive quantitative and qualitative analysis. From the study it was found that: 1) The developed teaching materials valid; 2) The practicality of the teaching material, viewed from the realization of the lesson plan, and the students activity is suitable with the steps of the œinternalization model; and 3) The teaching material is The effective viewed from (a) The mastery of students study on aspects of moral sensitivity; (b) The increase of moral sensitivity shown by 80,98% students after the learning process, and (c) Students response towards the teaching material and implementation reaches 98,15%, categorized as very strong. The result of the study showed that the teaching material using internalization model on subject matter ˜wave and sound is valid, practical, and effective to increase moral sensitivity of student in Junior High School. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran model pemaknaan pada materi gelombang dan bunyi yang valid, praktis, dan efektif untuk melatihkan sensitivitas moral siswa SMP. Pengembangan perangkat pembelajaran menggunakan model 4-D yang direduksi menjadi 3-D, yaitu define, design, dan develop dan diujicobakan di kelas VIII SMP Negeri 1 Ketapang dengan menggunakan One Group Pretest and Posttest Design. Pengumpulan data menggunakan metode pengamatan, pemberian tes, dokumentasi dan penyebaran angket. Teknik analisis data menggunakan analisis deskriptif kuantitatif dan kualitatif. Temuan hasil penelitian, yaitu: 1) Perangkat pembelajaran yang dikembangkan berkategori valid; 2) Kepraktisan perangkat pembelajaran ditinjau dari keterlaksanaan RPP dan aktivitas siswa sesuai dengan tahap-tahap pada model pemaknaan; dan 3) Perangkat pembelajaran efektif ditinjau dari: (a) Ketuntasan hasil belajar siswa pada aspek sensitivitas moral; (b) Peningkatan sensitivitas moral dengan kategori sensitif yang ditunjukkan 80,98% siswa setelah pembelajaran mencapai tingkatan sensitif, dan (c) Respon siswa terhadap perangkat dan pelaksanaan pembelajaran mencapai 98,15% dengan kriteria sangat kuat. Hasil penelitian menunjukkan bahwa perangkat pembelajaran model pemaknaan pada materi gelombang dan bunyi valid, praktis, dan efektif untuk melatihkan sensitivitas moral siswa SMP.